COMPARISON OF LABORATORY AC-WC MIX PERFORMANCE USING PETROLEUM ASPHALT PEN 60/70 POLYMER ASPHALT - Wardhana (NIM 25007025), Hendra
ABSTRACT: The resistance of pavement surface of Asphalt Concrete Wearing Course (AC-WC) to the traffic loading, the enviromental condition and the high temperature, depend primarily on the asphalt mixture. i.e. asphalt and aggregate. In recent years a decrease of Asphalt Concrete Wearing performance has been occurred. One alternative to improve pavement performance, was the use of polymer modified asphalt. The use of polymer modified asphalt (BituBale) in asphalt mixture is expected to improve the weakness of conventional asphalt (Shell non polymer Pen 60/70) and to increase its performance. The objectives of this study was to assess the mixture performance of an AC-WC modified by polymer as the cover of asphalt bitumen, called BituBale. The performance was physical characteristic of asphalt that would be compared to the Technical Specification, and the measurement of Resilient Modulus and Deformation resistance of mixture using the UMATTA machine testing and Wheel Track Machine (WTM) testing. The similar testing would be conducted with asphalt Shell non polymer Pen 60/70 as a comparison. The result of the asphalt rheology, conducted before and after TFOT, showed that BituBale asphalt has the sensitivity to temperature change at temperature range of 25 degrees C-45 degrees C. Saybolt-Furol viscosity test showed that BituBale asphalt has higher viscosity compared to Shell Pen 60/70 asphalt. The KAO value based on Marshall test combined with Percentage Refusal Density methods for the Shell Asphalt and BituBale asphalt are 5,73% and 5,53%. Respectively based on the laboratory testing result, the use of BituBale asphalt give better performance than the use of Shell asphalt. It is shown by the higher IKS value,i.e. 89,42% for polymer modified Asphalt (BiuBale) mixture and 88,71% for non polymer Shell asphalt mixture. Comparison of Resilient Modulus assessed by the UMATTA machine testing, showed that polymer modified asphalt (BituBale) mixture gave the lower Resilient Modulus value at testing temperatures of 25 degrees C, 35 degrees C and 45 degrees C (3582 MPa, 1387 MPa and 580,3 MPa) than that of non polymer Shell asphalt mixture (4666,0 MPa, 1474,0 MPa and 587,60 MPa), even so the result of Deformation Resistance test using WTM showed that modified polymer asphalt (BituBale) mixture had better resistance to deformation performance than the non polymer Shell aspahlt mixture, at temperature of 60 degrees C. Generally, the elastomeric modified polymer asphalt (BituBale) gave better performance than the non polymer Shell Asphalt especially for using at high temperature.